Ansiedad, depresión y estrategias de afrontamiento en una muestra de adultos desempleados de Riohacha, La Guajira. (2023)
This study examined the relationship between anxiety, depression, and coping strategies among unemployed adults in Riohacha, La Guajira, compared to a control group of employed individuals. The results indicated that the unemployed group exhibited a higher prevalence of anxiety and depression compared to the employed group. Additionally, notable differences were observed in the coping strategies employed by the two groups. The unemployed group was found to utilize the autonomy coping strategy more frequently to navigate their situation, while the employed group exhibited a higher tendency towards emotional avoidance. These findings 7 underscore the significance of addressing mental health concerns and developing effective coping mechanisms within the context of unemployment, providing valuable insights for designing interventions and appropriate support for unemployed individuals.